The Management of Eating Disorders and Obesity 1999
DOI: 10.1007/978-1-59259-694-2_14
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Treatment of Obesity

Abstract: SynopsisBehavioral treatment should be the first line of intervention for overweight and obese individuals. This paper provides an overview of the structure and principles of behavioral weight loss treatment. The short-and long-term effectiveness of this approach is reviewed. Strategies for improving weight loss maintenance are described, including prolonging contact between patients and providers (either in the clinic or via Internet or telephone), facilitating high amounts of physical activity, and combining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…However, the clinical significance of an 8.5 kg reduction in body weight is also determined by whether the weight loss is maintained over the long run. Reviews of randomized clinical trials of behavior therapy for obesity show that over the course of the year following behavioral treatment participants regain typically 30–40% of their lost weight (Brownell & Wadden, 1992; Perri & Fuller, 1995; Wadden & Sarwer, in press). The actual percentage of weight regain following behavior therapy may be somewhat higher than 30–40% because participants in some of the studies reviewed received additional treatment or maintenance therapy during the period immediately subsequent to initial treatment.…”
Section: Treatment Of Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the clinical significance of an 8.5 kg reduction in body weight is also determined by whether the weight loss is maintained over the long run. Reviews of randomized clinical trials of behavior therapy for obesity show that over the course of the year following behavioral treatment participants regain typically 30–40% of their lost weight (Brownell & Wadden, 1992; Perri & Fuller, 1995; Wadden & Sarwer, in press). The actual percentage of weight regain following behavior therapy may be somewhat higher than 30–40% because participants in some of the studies reviewed received additional treatment or maintenance therapy during the period immediately subsequent to initial treatment.…”
Section: Treatment Of Obesitymentioning
confidence: 99%
“…More than 150 studies have evaluated the effectiveness of behavior therapy for obesity. Recent reviews (Brownell & Wadden, 1992; Perri & Fuller, 1995; Wadden & Sarwer, in press) of randomized trials conducted in the past decade show that behavioral treatment, typically delivered in 15–24 weekly groups sessions, produced an average weight loss of approximately 8.5 kg, an amount that represented a mean body weight reduction of 9%. This degree of weight loss is associated with significant improvements in blood pressure and blood glucose (Kanders & Blackburn, 1992; Wing et al, 1987; Wing & Jeffery, 1995), and psychological well-being (Wadden & Stunkard, 1993).…”
Section: Treatment Of Obesitymentioning
confidence: 99%
“… 17 However, without follow‐up treatment, individuals often experience weight regain of 40%–50% within 1–2 years. 18 , 19 Transitioning individuals from a pro‐obesogenic lifestyle to a healthy one is crucial in obesity management as it involves modifying the habits and environment that contributed to the severity of obesity in the first place. Studies have indicated that combining VLCD therapy with intensive lifestyle changes leads to longer‐term weight reduction, which is more successful than VLCD therapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Long‐term weight loss, with or without bariatric surgery, is most effective in interventions that are the focused on behaviour change . To this end, obesity is influenced by learned behaviours . Post‐operative interventions such as BELT strive for long‐term success in promoting lifestyle modification for patients following bariatric surgery through inclusion of behavioural interventions.…”
Section: Discussionmentioning
confidence: 99%